Application Of Hand Massage Using Olive Oil And Jasmine To Reduce Anxiety Levels In Families Of Critical Patients - Laila Ulfiyana; Laili Ulfiyani; Putri Nurlia Anggraini; Sri Rahayu (Jurnal Keperawatan Profesional, 2026)
The care of critically ill patients in the ICU not only affects the patients’ condition but also places significant psychological strain on their families, particularly in the form of anxiety. Unmanaged anxiety can affect families’ ability to make decisions and participate in the care process. Non-pharmacological interventions such as hand massage and aromatherapy are potential approaches for reducing anxiety. This study aims to analyse the effectiveness of hand massage using olive and jasmine oils in reducing anxiety levels among the families of critically ill patients. The study employed a case study design with a pre-test and post-test approach involving 12 family members of patients in the ICU. The intervention was administered daily for three consecutive days, with each session lasting 15–30 minutes. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS). The results showed that prior to the intervention, the majority of respondents experienced severe anxiety (50%) and moderate anxiety (25%). Following the intervention, there was a reduction in anxiety, characterised by an increase in the ‘not anxious’ category (33.3%) and the ‘mild’ category (41.7%), as well as a decrease in severe anxiety to 8.3%, with no cases of panic observed. The mean anxiety score decreased from 2.58 ± 0.99 to 1.00 ± 1.04. It was concluded that hand massage with olive and jasmine oil is effective in reducing anxiety among the families of critically ill patients. This intervention may serve as an alternative non-pharmacological therapy in family-centred care nursing practice.